Anti-factor Xa Activity Is Not Associated With Venous Thromboembolism in Critically Ill Patients Receiving Enoxaparin for Thromboprophylaxis: A Retrospective Observational Study - Dibiasi, Christoph; Gratz, Johannes; Wiegele, Marion; Baierl, Andreas; Schaden, Eva (Frontiers in Medicine, 2022)
Background: Anti-factor Xa activity has been suggested as a surrogate parameter for judging the effectiveness of pharmacological thromboprophylaxis with low molecular weight heparins in critically ill patients. However, this practice is not supported by evidence associating low anti-factor Xa activity with venous thromboembolism. Methods: We performed a retrospective observational study including 1352 critically ill patients admitted to 6 intensive care units of the Medical University of Vienna, Austria between 01/2015 and 12/2018. Included patients received prophylactically dosed enoxaparin (≤ 100 IU/kg body weight per day). We analysed median peak, 12-hour trough and 24-hour trough anti-factor Xa activity per patient and compared anti-factor Xa activity between patients without versus with venous thromboembolic events. Results: 19 patients (1.4%) developed a total of 22 venous thromboembolic events. We did not observe a difference of median [IQR] anti-factor Xa activity between patients without venous thromboembolism (peak 0.22 IU/mL [0.14–0.32]; 12-hour trough 0.1 IU/mL [<0.1–0.17], 24-hour trough <0.1 IU/mL [<0.1–<0.1]) versus patients with venous thromboembolism (peak 0.33 IU/mL [0.14–0.34]; 12-hour trough 0.12 IU/mL [<0.1–0.26]; 24-hour trough <0.1 IU/mL [<0.1–<0.1]). Conclusions: Patients who developed venous thromboembolism had anti-factor Xa activities comparable to those who did not suffer from venous thromboembolism.